PSYCHOLOGY AMONG DIASPORA ARMENIAN SCIENTISTS - Takooshian, H. (Modern Psychology, 2019)
With over two-thirds of the world's 11 million Armenians living outside the Republic of Armenia today, how are Diaspora Armenians involved in psychological science and practice? It is notable that many Armenians are so active among the key behavioral scientists in the world today, across national borders. In this part, we will introduce 3 Diaspora Armenians, who describe their experiences and how Diaspora Armenians can more closely cooperate with colleagues in the Republic of Armenia.